1998
DOI: 10.1007/s11661-998-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and creep behavior of an orthorhombic Ti-25Al-17Nb-1Mo alloy

Abstract: Microstructural evolution during three heat-treatment schedules and the terminal microstructures in an orthorhombic alloy of Ti-25Al-17Nb-1Mo were observed and analyzed with optical microscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The creep behavior of the alloy with three different microstructures (a coarse-lath, fine-lath, and fine equiaxed microstructure) was studied over a temperature range of 600 ЊC to 750 ЊC and over a stress range of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Over the stress range of 34 to 75 MPa, the creep stress exponent transitioned to a value of 2.6, and a Q app value of 217 kJ/mol was measured at r = 75 MPa. The n values obtained within both stress regimes are in agreement with those previously reported for O + bcc Ti-Al-Nb alloys; [9][10][11][12][13][14]16,[24][25][26] however, the Q app values tended to be lower. The Q app values determined from creep experiments in the intermediate-stress and high-stress regime at 650°C for fully-O and O + bcc alloys fall in the range of 256 to 376 kJ/mol.…”
Section: B Creep Behaviorsupporting
confidence: 90%
See 1 more Smart Citation
“…Over the stress range of 34 to 75 MPa, the creep stress exponent transitioned to a value of 2.6, and a Q app value of 217 kJ/mol was measured at r = 75 MPa. The n values obtained within both stress regimes are in agreement with those previously reported for O + bcc Ti-Al-Nb alloys; [9][10][11][12][13][14]16,[24][25][26] however, the Q app values tended to be lower. The Q app values determined from creep experiments in the intermediate-stress and high-stress regime at 650°C for fully-O and O + bcc alloys fall in the range of 256 to 376 kJ/mol.…”
Section: B Creep Behaviorsupporting
confidence: 90%
“…Several studies have focused on constructing microstructure-creep relationships and determining creep deformation mechanisms [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and constructing microstructure-tensile relationships of two-phase O + bcc Ti-Al-Nb alloys. [6,8,16,[18][19][20][21][22][23]25,[27][28][29][30][31][32][33] To some extent, the tensile and creep properties of fully-O microstructures and the tensile properties of fully-bcc microstructures have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Alloys containing Nb less than 12 at. pct have a two-phase microstructure a 2 (hcp structure based on Ti 3 Al) and the high-temperature phase b/B2 (bcc structure).…”
Section: Introductionmentioning
confidence: 99%
“…The Ti 2 AlNb-based alloys with a two-phase microstructure (orthorhombic-bcc) are known to have better mechanical properties than those of conventional alpha-2 based alloys [3]. Since the microstructure of Ti 2 AlNb alloy can be easily controlled with various heat-treatment schedules [4][5][6][7][8], the relationship between microstructure/mechanical properties have been frequently reported in the last decade [9][10][11][12]. In these reports, attention has been focused on the modified microstructures and heat-treatment processes to achieve a good balance of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In these reports, attention has been focused on the modified microstructures and heat-treatment processes to achieve a good balance of mechanical properties. The transient creep behavior of primary strain [11,13] and the calculation of apparent creep activation energy of different Ti 2 AlNb-based alloys [10,[12][13][14][15] have been investigated. It has been reported that the tensile strength of O + bcc dual phase alloys is significantly decreased above 700 • C regardless of aging condition and alloy composition.…”
Section: Introductionmentioning
confidence: 99%